The effect of intercritical heat treatment on the mechanical properties of AISI 3115 steel - Maleque, Md. Abdul; Poon, Y. M.; Masjuki, H. H. (Elsevier BV, 2004)
This paper presents the effect of intercritical heat treatment (IHT) on the mechanical properties of AISI 3115 alloy steel. The steel was intercritically heat-treated at a temperature range of 730–830 ◦C followed by water quenching. The properties of tensile strength, fatigue, hardness and microstructure were evaluated from the mechanical tests and metallographic analysis, respectively. The experimental results showed that tensile strength increases but impact strength decreases with increasing intercritical emperature, correspondingly with the increase in amount of martensite in the steel. It was found that the resulting microstructures are predominantly ferrite with martensite, which is known as ‘dual-phase steels’. This indicates that both the soft and ductile ferrite matrix and strong and tough martensite particles play an important role in determining the dual-phase properties, especially continuous yielding behaviour of the steel. The fractographic analysis results are also discussed in this paper.